2004
DOI: 10.1111/j.1365-2249.2004.02607.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-10, IL-1ra and IL-12 profiles in active and quiescent systemic lupus erythematosus: could longitudinal studies reveal patient subgroups of differing pathology?

Abstract: SUMMARYSeveral cytokines have been implicated individually in the pathogenesis of systemic lupus erythematosus (SLE) and some, including interleukin (IL)-10, IL-12 and IL-1ra are raised during flares of disease activity. Few studies have been directed at examining the interactions between these cytokines and how their combined profile relates to disease activity. We have examined serum levels of IL-10, IL-12 and IL1ra in a cohort of SLE patients obtained from the Queen Elizabeth Hospital, Birmingham in crossse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 39 publications
4
29
2
1
Order By: Relevance
“…This data is in accordance with previous reports [26,36]. This might be indicated to the participation of Dendritic cells (DCs) in SLE as it represents the main IL-12 producer cells [37].…”
Section: Discussionsupporting
confidence: 95%
“…This data is in accordance with previous reports [26,36]. This might be indicated to the participation of Dendritic cells (DCs) in SLE as it represents the main IL-12 producer cells [37].…”
Section: Discussionsupporting
confidence: 95%
“…Earlier observations on the increased serum level of IL-1Ra in SLE patients are convincing, but their relations to the disease activity show contradictions [7,16,23,24]. According to our present results, there is a rather high, significant and concomitant elevation in the serum levels of both IL-1Ra and CRP, and these increases correlate significantly in all groups of SLE patients, but there was a correlation with SLEDAI only in ILN patients.…”
Section: Discussioncontrasting
confidence: 77%
“…19,20 However, in the present study, the IL-10 level in the EBC was found to correlate negatively with the activity of SLE, and it showed a similar tendency in the BALF. This finding could confirm that of Capper et al 18 regarding the coexistence of groups of SLE patients with different patterns of cytokine activity. They found a group of patients with a completely different cytokine profile to that of other SLE patients; the differences could be due to varied etiologies of SLE.…”
supporting
confidence: 82%
“…16 The disease severity correlates with elevated IL-10 concentrations. 17,18 The serum levels the percentage of alveolar macrophages in BALF (r = 0.39, P = 0.02), FEV 1 (r = 0.43, P = 0.022), and FVC (r = 0.40, P = 0.035). It was negatively correlated with the percentage of lymphocytes in BALF (r = -0.43, P = 0.011).…”
mentioning
confidence: 99%